Integrating Circular Economy Practices for Sustainable Maritime Tourism Development in Bone Regency, Indonesia - Hasnawati Hasnawati; Irmawati Irmawati (Mahesa Research Center, 2024)
This study analyzes the application of circular economy principles in the development of marine tourism in Bone Regency, Indonesia, using a qualitative case study approach involving local government representatives, community members, and tourists. Data was collected through in-depth interviews and field observations to understand the integration of circular economy practices, including waste management, resource reuse, and local community empowerment. Findings highlight both opportunities and challenges in implementing sustainable tourism, such as limited funding and infrastructure. However, effective practices, such as community-led recycling initiatives and government support in waste treatment, underscore the potential for circular economy models to enhance environmental sustainability and local economic benefits. The study concludes that a circular economy framework, supported by multi-stakeholder collaboration, can provide a path toward sustainable marine tourism, offering insights for policymakers and researchers aiming to balance environmental and economic goals in tourism development.